A critical review on diabetes mellitus type 1 and type 2 management approaches: from lifestyle modification to current and novel targets and therapeutic agents - Tegegne, Bantayehu Addis; Adugna, Adane; Yenet, Aderaw; Yihunie Belay, Wubetu; Yibeltal, Yared; Dagne, Abebe; Hibstu Teffera, Zigale; Amare, Gashaw Azanaw; Abebaw, Desalegn; Tewabe, Haymanot; Abebe, Rahel Belete; Zeleke, Tirsit Ketsela (Frontiers in Endocrinology, 2024)
Diabetes mellitus (DM) has emerged as an international health epidemic due to its rapid rise in prevalence. Consequently, scientists and or researchers will continue to find novel, safe, effective, and affordable anti-diabetic medications. The goal of this review is to provide a thorough overview of the role that lifestyle changes play in managing diabetes, as well as the standard medications that are currently being used to treat the condition and the most recent advancements in the development of novel medical treatments that may be used as future interventions for the disease. A literature search was conducted using research databases such as PubMed, Web of Science, Scopus, ScienceDirect, Wiley Online Library, Google Scholar, etc. Data were then abstracted from these publications using words or Phrases like -pathophysiology of diabetes‖, -Signe and symptoms of diabetes‖, -types of diabetes‖, -major risk factors and complication of diabetes‖, -diagnosis of diabetes‖, -lifestyle modification for diabetes‖, -current antidiabetic agents‖, and -novel drugs and targets for diabetes management‖ that were published in English and had a strong scientific foundation. Special emphasis was given to the importance of lifestyle modification, as well as current, novel, and emerging/promising drugs and targets helpful for the management of both T1DM and T2DM.